High-throughput artifact-free slightly off-axis holographic imaging based on Fourier ptychographic reconstruction - Shen, Qian; Sun, Jiasong; Fan, Yao; Li, Zhuoshi; Gao, Peng; Chen, Qian; Zuo, Chao (Frontiers in Photonics, 2022)
Slightly off-axis digital holographic microscopy has recently gained considerable attention due to its unique ability to improve the space-bandwidth product (SBP) of the imaging system while separating the object information from the background intensity to a certain extent. In order to obtain a decent image reconstruction, the spectral aliasing problem still needs to be addressed, which, however, is difficult to be achieved by the conventional linear Fourier domain filtering. To this end, in this paper, we propose a high-throughput artifact-free slightly off-axis holographic reconstruction method based on Fourier ptychographic microscopy (FPM). Inspired by the nonlinear optimized phase reconstruction algorithm of FPM, we perform constrained updates between the object and Fourier domains in an iterative manner to reconstruct the complex amplitude by the hologram intensity. Experimental results on live HeLa cell samples show that the proposed method can provide higher reconstruction accuracy and better image quality compared with the conventional Fourier method and the Kramers-Kronig (KK) relation-based method.